Soft Exoskeleton Mimics Human Cough for Assisting the Expectoration Capability of SCI Patients - Zhang, Yan; Wang, Ziqi; Ge, Qinggang; Wang, Zongyu; Zhou, Xiangjie; Han, Shaohang; Guo, Weidong; Zhang, Yuru; Wang, Dangxiao (IEEE transactions on neural systems and rehabilitation engineering, 2022)
This paper describes the design of a bionic soft exoskeleton and demonstrates its feasibility for assisting the expectoration function rehabilitation of patients with spinal cord injury (SCI). Methods: A human-robot coupling respiratory mechanic model is established to mimic human cough, and a synergic inspire-expire assistance strategy is proposed to maximize the peak expiratory flow (PEF), the key metric for promoting cough intensity. The negative pressure module of the exoskeleton is a soft "iron lung" using layer-jamming actuation. It assists inspiration by increasing insufflation to mimic diaphragm and intercostal muscle contraction. The positive pressure module exploits soft origami actuators for assistive expiration; it pressures human abdomen and bionically "pushes" the diaphragm upward. Results: The maximum increase in PEF ratios for mannequins, healthy participants, and patients with SCI with robotic assistance were 57.67%, 278.10%, and 124.47%, respectively. The soft exoskeleton assisted one tetraplegic SCI patient to cough up phlegm successfully. Conclusion: The experimental results suggest that the proposed soft exoskeleton is promising for assisting the expectoration ability of SCI patients in everyday life scenarios. Significance: The proposed soft exoskeleton is promising for advancing the application field of rehabilitation exoskeletons from motor functions to respiratory functions.